Florida cities pay up after crippling ransomware attacks. Issue 7 (July 2019) - Unknown
Abstract : A series of ransomware attacks against city authorities in Florida, US, is proving lucrative for cyber criminals. Two cities have already decided to pay the ransoms and a third may follow.